Sugarcane Bagasse Fibers Reinforced in Polyurethane for Sorption of Vegetal Oil - Gandara, Meriane; Mulinari, D. R.; Monticeli, Francisco Maciel [UNESP]; Capri, M. R. (Taylor & Francis, 2020)
To enhance the removal of vegetal oil from water, the influence of the concentration of fibers from sugarcane bagasse pretreated by the steam explosion as reinforcement in polyurethane foam was used. The composites were obtained by mass mixing the polyol with the prepolymer (1: 1) and reinforced with 5% to 20% (wt/wt) sugarcane bagasse fibers. The fibers, composites and pure polyurethane were characterized by scanning electron microscopy (SEM), X-Ray Diffraction (XRD) and Surface area measurements (BET). Sorption tests were carried out on the fibers, pure polyurethane (PU) and composites. The sorption capacity of the composites was evaluated as a function of the fiber content inserted in the matrix. When applied as the oil sorbents, it was found that the composites reinforced with pretreated fibers presented better results, due to defibrillation of the fiber and the increase of its contact area dispersed in the polymer. Efficient removal increases with increasing concentration of fibers reinforced in polyurethane.
Keywords: composites; oil retention; oil sorption; polyurethane; Sugarcane bagasse; surface treatment